2021
DOI: 10.1101/2021.11.23.469762
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

In vitro and in vivo CRISPR-Cas9 screens reveal drivers of aging in neural stem cells of the brain

Abstract: Aging impairs the ability of neural stem cells to transition from quiescence to activation (proliferation) in the adult mammalian brain. Neural stem cell (NSC) functional decline results in decreased production of new neurons and defective regeneration upon injury during aging1–9, and this is exacerbated in Alzheimer’s disease10. Many genes are upregulated with age in NSCs3, 11–13, and the knockout of some of these boosts old NSC activation and rejuvenates aspects of old brain function14–18. But systematic fun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 107 publications
1
6
0
Order By: Relevance
“…For validation, we utilized a recently published dataset 54 ( Figure 5G , left) that employed a genome-wide CRISPR screen to systematically dissect the roles of various genes in neurogenesis by quantifying the enrichment of gene-specific single-guide RNAs (sgRNAs) within proliferation-active (Ki67+) primary neural stem cells in vitro . We examined the downregulated genes in aged NPCs ( Figure 5G , middle) and detected a significant reduction in their sgRNA enrichment compared to a set of randomly chosen genes ( Figure 5G , right).…”
Section: Resultsmentioning
confidence: 99%
“…For validation, we utilized a recently published dataset 54 ( Figure 5G , left) that employed a genome-wide CRISPR screen to systematically dissect the roles of various genes in neurogenesis by quantifying the enrichment of gene-specific single-guide RNAs (sgRNAs) within proliferation-active (Ki67+) primary neural stem cells in vitro . We examined the downregulated genes in aged NPCs ( Figure 5G , middle) and detected a significant reduction in their sgRNA enrichment compared to a set of randomly chosen genes ( Figure 5G , right).…”
Section: Resultsmentioning
confidence: 99%
“…Although the functional implications of these two genes in the context of aging remain unexplored, a recent study showed that knockout of genes encoding glucose import, such as Slc2a4 (encodes the GLUT4 glucose transporter), rejuvenated old NSCs. 53 Another top gene, Cd34 , which encodes endothelial cell glycoprotein, has been implicated in degeneration. 54 Thus, interpretation of the ELN model identifies potential genes related to the aging process.…”
Section: Resultsmentioning
confidence: 99%
“…While hPSC-derived 2D and 3D neural systems are well suited to recapitulate features of the developing fetal brain, it could be challenging to use them to model the aging brain and its related disorders. In this regard in vivo CRISPR screens are gaining traction ( Wertz et al, 2020 ; Ruetz et al, 2021 ). A recent study utilized both in vitro and in vivo CRISPR screening platforms in old mice and uncovered over 300 factors that boosted the activation of aged neural stem cells (NSCs) ( Ruetz et al, 2021 ).…”
Section: Experimental Considerations Limitations and Future Directionsmentioning
confidence: 99%
“…In this regard in vivo CRISPR screens are gaining traction ( Wertz et al, 2020 ; Ruetz et al, 2021 ). A recent study utilized both in vitro and in vivo CRISPR screening platforms in old mice and uncovered over 300 factors that boosted the activation of aged neural stem cells (NSCs) ( Ruetz et al, 2021 ). The in vivo screen was useful to validate top hits from the in vitro screen performed in primary NSCs from old mice.…”
Section: Experimental Considerations Limitations and Future Directionsmentioning
confidence: 99%